Ultrafast ID – VG Technique for Reliable Cryogenic Device Characterization - Pragya R. Shrestha; Akin Akturk; Brian Hoskins; Advait Madhavan; Jason P. Campbell (IEEE Journal of the Electron Devices Society, 2023)
An in-depth understanding of the transient operation of devices at cryogenic temperatures remains experimentally elusive. However, the impact of these transients has recently become important in efforts to develop both electronics to support quantum information science as well as cryogenic high-performance computing. In this paper, we discuss a fast time-dependent device characterization technique, capable of examining the charge trapping dynamics of devices operating at cryogenic temperatures. Careful calibrations allow for the acquisition of accurate fast I-V and transconductance transients down to 20 ns for devices operating down to 8 K. The trap charging dynamics was monitored via shifts in both threshold voltage and transconductance. The combination of fast measurements and cold temperatures were used to shift the observable measurement window to reveal charge trapping/de-trapping time dynamics of both fast and slow traps in high-k devices to demonstrate the utility of the fast I-V for cryogenic device characterization.